Adherencia al tratamiento y efectividad de un programa cognitivo conductual sobre la rumiación y expresión de la ira - Alcázar-Olán, Raúl José; Merckel-Niehus, Nicole; Toscano-Barranco, Daniela; Barrera-Muñoz, Omar; Proal-Sánchez, María Fernanda (Revista de Psicopatología y Psicología Clínica, 2018)
Abstract: Treatment adherence and effectiveness of a cognitive behavioral program on rumination and anger expression. This research assessed the effects of a cognitive behavioral intervention in a group of 30 individuals with anger and rumination problems. Two groups were compared. The first group of participants attended seven or more sessions (high attendance), while the second group attended less than seven sessions (low attendance). Only the group with high attendance showed statistically significant changes in variables such as revenge, angry afterthoughts, angry memories, and understanding the causes of anger. However, both groups improved in the same proportion, according to the strong effect sizes. Participants who attended less than seven sessions reported that they missed sessions due to academic reasons (doing homework). Participants with high attendance reported they showed up to sessions due to their achievements obtained with the treatment. Resumen: Esta investigación evaluó los efectos de una intervención cognitivo conductual grupal en 30 individuos con problemas de rumiación e ira. Se compararon dos grupos. El primero se formó de participantes que asistieron siete o más sesiones (alta asistencia), mientras que en el segundo los participantes asistieron menos de siete sesiones (baja asistencia). Se observaron mejoras estadísticamente significativas únicamente en el grupo con alta asistencia en variables de venganza, pensamientos posteriores a la ira, memorias de ira y entendimiento de las causas de la ira. Sin embargo, ambos grupos mejoraron en la misma proporción, lo cual se reflejó en tamaño del efecto fuerte. Los participantes que asistieron menos de siete sesiones informaron que su ausencia se debió a motivos académicos (hacer tareas). Los participantes con alta asistencia informaron que las razones para presentarse a las sesiones fueron los logros que obtenían con el tratamiento.